THE The Application of TOPSIS Method and Djikstra Algorithm in The Development of Potential Tourist Attractions on The Jakarta to Dieng Route - Wiwit Rifayanto; Luqman; Herman Bedi; Rizqia Cahyaningtyas (Politeknik Piksi Ganesha Indonesia, 2025)
Finding the optimal route for several vehicles in determining destinations according to their travel needs, such as serving customers, finding places for tourism, finding destinations for personal, family, or community touring, or logistical distribution, has become an essential need today. Route selection with considerations of fuel cost savings, tolls, regional levies, dining or rest stops, and fuel refilling stations (gas stations) is also a critical basis for achieving travel objectives. This research was conducted through surveys of alternative routes from Jakarta to Dieng in Central Java, and interviews with motorcycle users for this journey (Motor Touring) conducted by a motorcycle community. The application of the TOPSIS method, which is then compared with the results of the Dijkstra Algorithm in determining a route, can be a solution in route selection, in this case, the route from Jakarta to Dieng (Central Java). Alternative routes with attributes such as route, travel time, road conditions, fuel refilling locations, and rest stops for meals or just drinks become significant factors considered by motorcycle enthusiasts for touring to a region. The selection of the right route recommendation makes this route the primary choice for motor vehicle users, with the busy traffic on this route positively impacting the local residents, who were previously vegetable or fruit farmers, by providing additional income through selling snacks, ready-to-eat meals, coffee, parking, rest areas, toilets, and necessities for the stay in Dieng, such as gloves, hats, and jackets.